Algebra 1

Published by Prentice Hall
ISBN 10: 0133500403
ISBN 13: 978-0-13350-040-0

Chapter 7 - Exponents and Exponential Functions - 7-5 Division Properties of Exponents - Practice and Problem-Solving Exercises - Page 445: 73



Work Step by Step

=$\frac{(\frac{1}{4})^{-2}}{(\frac{1}{6})^{-3}}$ =$\frac{\frac{1}{4^{-2}}}{\frac{1}{6^{-3}}}$ =$\frac{4^{2}}{6^{3}}$ =$\frac{16}{216}$ =$\frac{2}{27}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.